Modeled buoyancy of eggs and larvae of the deep-sea shrimp Aristeus antennatus (Crustacea: Decapoda) in the northwestern Mediterranean Sea - Clavel-Henry, Morane (PLoS One, 2020)
Information on the buoyancy of eggs and larvae from deep-sea species is rare but necessary for explaining the position of non-swimming larvae in the water column. Due to embryonic morphology and ecology diversities, egg buoyancy has important variations within one species and among other ones. Nevertheless, it has hardly been explored if this buoyancy variability can be a strategy for deep-sea larvae to optimize their transport beyond their spawning areas. In the northwestern Mediterranean Sea, protozoea and mysis larvae of the commercial deep-sea shrimp Aristeus antennatus were recently found in upper layers, but to present, earlier stages like eggs and nauplii have not been collected. Using a Lagrangian transport model and larval characteristics, we evaluate the buoyancy and hydrodynamic effects on the transport of A. antennatus’ larvae in the northwestern Mediterranean Sea. The transport models suggested that 75% of buoyant eggs released between 500 and 800 m depth (i.e., known spawning area), reached the upper water layers (0–75 m depth). Then, according to the modeled larval drifts, three spawning regions were defined in the studied area: 1) the northern part, along a continental margin crossed by large submarine canyons; 2) the central part, with two circular circulation structures (i.e., eddies); and 3) the southern part, with currents flowing through a channel. The number of larvae in the most upper layer (0–5 m depth) was higher if the larval transport model accounted for the ascent of eggs and nauplii (81%) instead of eggs reaching the surface before hatching (50%). The larvae reaching the most water upper layer (0–5 m depth) had higher rates of dispersal than the ones transported below the surface layer (deeper than 5 m depth). The results of larval dispersal simulations have implications for the understanding of A. antennatus larval ecology and for management decisions related to the shrimp fisheries in the northwestern Mediterranean Sea.